Soliton-cuspon interaction for the Camassa-Holm equation - Ferreira, M. C.; Kraenkel, Roberto André [UNESP]; Zenchuk, A. I. (Iop Publishing Ltd, 1999)
The interaction of different kinds of solitary waves of the Camassa-Holm equation is investigated. We consider soliton-soliton, soliton-cuspon and cuspon-cuspon interactions. The description of these solutions had previously been shown to be reducible to the solution of an algebraic equation. Here we give explicit examples, numerically solving these algebraic equations and plotting the corresponding solutions. Further, we show that the interaction is elastic and leads to a shift in the position of the solitons or cuspons. We give the analytical expressions for this shift and represent graphically the coupled soliton-cuspon, soliton-soliton and cuspon-cuspon interactions.